A Study on Behavioral Intention and Use Behavior Toward Mobile Payment Among University Students in Nanning, China - Tang, Zehua (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: The study examines key factors influencing behavioral intention and actual use of mobile payment services among university students in Nanning, China. The proposed framework explores the relationships among Social Influence (SI), Effort Expectancy (EE), Trust (TS), Perceived Usefulness (PU), Perceived Risk (PR), Habit (HB), Behavioral Intention (BI), and Use Behavior (UB). Research design, data and methodology: The researcher conducted a questionnaire survey among 500 university students in Nanning, China. Participants were purposefully selected from four main colleges of Guangxi University, following stratified random sampling guidelines. Data were collected online using a convenience sampling approach. For analysis, CFA and SEM were applied to evaluate model fit, reliability, and structural validity. Results: The findings indicate that social influence, effort expectancy, trust, perceived usefulness, perceived risk, and habit significantly affect behavioral intention. Behavioral intention, in turn, strongly influences use behavior. Among these factors, perceived usefulness had the greatest impact on behavioral intention, followed by trust and social influence. Conclusions: The statistical results supported all seven research hypotheses, confirming that the study successfully met its objectives. To enhance mobile payment adoption, policymakers and service providers should prioritize key influencing factors and implement effective optimization strategies.